Squeeze this! : a cultural history of the accordion in America - Jacobson, Marion S. (Folklore studies in a multicultural world., 2012)
Squeeze This! is the first history of the piano accordion and the first book-length study of the accordion as a uniquely American musical and cultural phenomenon.